GTR1 Affects Nitrogen Consumption and TORC1 Activity in Saccharomyces cerevisiae Under Fermentation Conditions - Molinet, Jennifer; Salinas, Francisco; Guillamón, José Manuel; Martínez, Claudio (Frontiers in Genetics, 2020)
The TORC1 pathway coordinates cell growth in response to nitrogen availability present in the medium, regulating genes related to nitrogen transport and metabolism. Therefore, the adaptation of Saccharomyces cerevisiae to changes in nitrogen availability implies variations in the activity of this signaling pathway. In this sense, variations in nitrogen detection and signaling pathway are one of the main causes of differences in nitrogen assimilation during alcoholic fermentation. Previously, we demonstrated that allelic variants in the GTR1 gene underlying differences in ammonium and amino acids consumption between Wine/European (WE) and West African (WA) strains impact the expression of nitrogen transporters. The GTR1 gene encodes a GTPase that participates in the EGO complex responsible for TORC1 activation in response to amino acids availability. In this work, we assessed the role of the GTR1 gene on nitrogen consumption under fermentation conditions, using a high sugar concentration medium with nitrogen limitation and in the context of the WE and WA genetic backgrounds. The gtr1Δ mutant presented a reduced TORC1 activity and increased expression levels of nitrogen transporters, which in turn favored ammonium consumption, but decreased amino acid assimilation. Furthermore, to identify the SNPs responsible for differences in nitrogen consumption during alcoholic fermentation, we studied the polymorphisms present in the GTR1 gene. We carried out swapping experiments for the promoter and coding regions of GTR1 between the WE and WA strains. We observed that polymorphisms in the coding region of the WA GTR1 gene are relevant for TORC1 activity. Altogether, our results highlight the role of the GTR1 gene on nitrogen consumption in S. cerevisiae under fermentation conditions.